2013
DOI: 10.1016/j.appet.2013.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Emotional eating and food intake after sadness and joy

Abstract: Abstract:Do people with a high score on a scale for eating in response to negative emotions also show high food intake in response to positive emotions?. We studied these effects in 60 female students that were preselected on the basis of extreme high or low scores on an emotional eating questionnaire. Using a between subject design we experimentally tested the difference in food intake following a mood induction designed to induce joy or sadness (the joy vs. sad mood condition). The high and low emotional eat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
134
1
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(179 citation statements)
references
References 23 publications
15
134
1
15
Order By: Relevance
“…In addition, obesity signifies non-adaptive coping strategies and the regulation of emotional state through food [54]. There is a high probability that due to strong stigmatization and alienation, individuals with obesity are faced with negative emotions and cope by engaging in (emotional) eating [55][56][57][58]. Determinants of BMI can also be configured in various styles of eating: cognitive restraint (vs. unrestrained), uncontrolled eating (vs. controlled) and emotional eating (vs. unemotional) [30,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, obesity signifies non-adaptive coping strategies and the regulation of emotional state through food [54]. There is a high probability that due to strong stigmatization and alienation, individuals with obesity are faced with negative emotions and cope by engaging in (emotional) eating [55][56][57][58]. Determinants of BMI can also be configured in various styles of eating: cognitive restraint (vs. unrestrained), uncontrolled eating (vs. controlled) and emotional eating (vs. unemotional) [30,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, emotional eating increases the intake of sweet and fatty foods, or 'comfort food' (90)(91)(92) . In experimental studies, emotional eaters have been found to consume more sweet and fatty foods (93)(94)(95) in response to stress. Although there are fewer studies of child populations, the conclusions are often similar: emotional eating was associated with high intake of sweet and/ or fatty food in both observational (85,(96)(97)(98) and laboratory studies (95,(99)(100)(101) .…”
Section: Nutrition Research Reviewsmentioning
confidence: 99%
“…Regarding comparison of the DLS video with previously validated videos, other studies have also mentioned an increase in negative emotions and a reduction in positive emotions after presentation of this type of video (Macht & Mueller, 2007;Sheppard-Sawyer et al, 2000;van Strien et al, 2013;Yeomans & Coughlan, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The movies validated to manipulate emotions are videos that stimulate fear, incite anger, and foster happiness (Bongers, Jansen, Havermans, Roefs, & Nederkoorn, 2013;Gross & Levenson, 1995;Macht & Mueller, 2007;Philippot, 1993;van Strien et al, 2013;Yeomans & Coughlan, 2009). These movies have effectively aided investigation of specific emotions.…”
Section: Introductionmentioning
confidence: 99%